The Effectiveness of Compassion-based Therapy on Rumination and Concern in Patients with Type I Diabetes - Zahra Dabbaghha; Alireza Mollazadeh (Iranian Journal of Diabetes and Obesity)
Objective: According to the studies, 80% of patients with diabetes suffer from concern and rumination in their life cycle. The present study aimed to investigate the effectiveness of compassion-based therapy (CBT) on rumination and concern in patients with type 1 diabetes. Materials and Methods: A quasi-experimental study evaluated the effect of CBT on women with type 1 diabetes. Thirty women with type 1 diabetes, recruited from Qazvin city health centers between October 2024 and March 2025 and meeting inclusion criteria, were purposively sampled and randomly assigned to the CBT (n= 15) or control (n= 15) group. The intervention group received eight weekly 90-minute sessions. The control group received no intervention. The Pennsylvania State Worry Questionnaire (PSWQ) and Rumination Questionnaire (RQ) were administered pre- and post-intervention, and data were analyzed using ANCOVA in SPSS version 26. Results: A comprehensive analysis of variance has revealed notable disparities between the experimental and control groups in terms of worry and rumination. The results indicate a moderate effect size for worry (η= 0.29; F= 10.63; P= 0.003). Similarly, rumination also shows a strong effect size (η= 0.39; F= 17.23; P< 0.001). Conclusion: CBT effectively reduces rumination and worry in patients with type I diabetes in Qazvin, suggesting its potential as a supportive treatment for these symptoms